Anisotropic thermoelectric effect and field-effect devices in epitaxial bismuthene on Si (111). (2nd September 2020) - Zhong, Wen; Zhao, Yu; Zhu, Beibei; Sha, Jingjie; Walker, Emily S; Bank, Seth; Chen, Yunfei; Akinwande, Deji; Tao, Li
Abstract: This experimental study reveals intriguing thermoelectric effects and devices in epitaxial bismuthene, two-dimensional (2D) bismuth with thickness ⩽30 nm, on Si (111). Bismuthene exhibits interesting anisotropic Seebeck coefficients varying 2–5 times along different crystal orientations, implying the existence of a puckered atomic structure like black phosphorus. An absolute value of Seebeck coefficient up to 237 μ V K −1 sets a record for elemental Bi ever measured to the best of our knowledge. Electrical conductivity of bismuthene can reach up to 4.6 × 10 4 S m −1, which is sensitive to thickness and magnetic field. Along with a desired low thermal conductivity ∼1.97 W m −1 K that is 20% of its bulk form, the first experimental zT value at room temperature for bismuthene was measured ∼10 –2, which is much higher than many other VA Xenes and comparable to its bulk compounds. Above results suggest a mixed buckled and puckered Bi atomic structure for epitaxial 2D bismuth on Si (111). Our work paves the way to explore potential applications, such as heat flux sensor, energy converting devices and so on for bismuthene.